Understanding sport tourists' motives and perceptions of Sabah, Malaysia as a sport tourist destination - Dolinting, Erica E.; Yusof, Aminuddin; Chee, Chen Soon (University of Pitesti, Romania, 2013)
With the focus on Mount Kinabalu as a sport tourism destination, the push and pull theory (Dann, 1981) was adopted as framework to examine the travel motivation of sport tourists visiting Sabah, Malaysia. The Leisure Motivation Scale (Beard & Ragheb, 1983) and semantic differential instrument by Attle (1996) were utilized to measure the push motives and pull factors. Analyses of data include descriptive statistics, t-test and logistic regression. A sample of 195 mountain climbers was selected with the majority comprising of international active sport tourists respondents (71.1%). Statistically, domestic active sport tourists at Mount Kinabalu were more significantly motivated by two out of four push motives namely; competence-mastery and social factors. With respect to the pull factors, analysis of result from the logistic regression shows there were few attributes which has been identified to be perceived differently by the domestic and international tourists. The findings of the study implied that: (1) market segmentations can be made according to the demographic and travel characteristics information as well as by their travel motivations among domestics and internationals sport tourists; (2) theoretical significance and practical marketing implications in addition with the recommendations for local tourism authority, destination managers and marketers are discussed.